Nano transdermal system combining mitochondria-targeting cerium oxide nanoparticles with all-trans retinoic acid for psoriasis - Wei Wang; Xinyi Xu; Yanling Song; Lan Lan; Jun Wang; Xinchang Xu; Yongzhong Du (Elsevier, 2023)
Psoriasis is an inflammatory skin disease that is intricately linked to oxidative stress. Antioxidation and inhibition of abnormal proliferation of keratinocytes are pivotal strategies for psoriasis. Delivering drugs with these effects to the site of skin lesions is a challenge that needs to be solved. Herein, we reported a nanotransdermal delivery system composed of all-trans retinoic acid (TRA), triphenylphosphine (TPP)-modified cerium oxide (CeO2) nanoparticles, flexible nanoliposomes and gels (TCeO2-TRA-FNL-Gel). The results revealed that TCeO2 synthesized by the anti-micelle method, with a size of approximately 5 nm, possessed excellent mitochondrial targeting ability and valence conversion capability related to scavenging reactive oxygen species (ROS). TCeO2-TRA-FNL prepared by the film dispersion method, with a size of approximately 70 nm, showed high drug encapsulation efficiency (>96%). TCeO2-TRA-FNL-Gel further showed sustained drug release behaviors, great transdermal permeation ability, and greater skin retention than the free TRA. The results of in vitro EGF-induced and H2O2-induced models suggested that TCeO2-TRA-FNL effectively reduced the level of inflammation and alleviated oxidative stress in HaCat cells. The results of in vivo imiquimod (IMQ)-induced model indicated that TCeO2-TRA-FNL-Gel could greatly alleviate the psoriasis symptoms. In summary, the transdermal drug delivery system designed in this study has shown excellent therapeutic effects on psoriasis and is prospective for the safe and accurate therapy of psoriasis.